Pengaruh Karakteristik Personal dan Karakteristik Pekerjaan terhadap Komitmen Organisasional Perawat - Wiwit Ekayanti; Susi Widjajani; Budiyanto Budiyanto (Universitas Proklamasi 45 Yogyakarta, 2019)
This study aims to examine the effect of personal characteristics and job characteristics on organizational commitment of hospital nurses. Employee organiza-tional commitment can be influenced by many factors, including personal charac-teristics and job characteristics. They are the factors form the initial organizational commitment that can affect the ups and downs of employee organizational commitment. The population in this study were hospital nurses in Gombong, Indonesia and the sample of this study was 75 respondents taken by a simple random sampling technique. The data collection technique in this study used a questionnaire with a Likert scale. The main instrument used to obtain data is arranged systematically containing several statements given to respondents who have met the requirements for validity and reliabi-lity. Data analysis used multiple linear regression and the hypothesis testing analysis applied partial significance test. The results showed a positive and significant influence of personal characteristics and job characteristics partially on organizational commit-ment. The implications of the results of this study can be applied in hospitals to build the commitment of nurses through job characteristics and personal characteristics. Further research should use other independent variables outside of this study with a larger number of respondents.